Analisis Kesesuaian Bahan Ajar Pada Buku Senang Belajar Matematika Kelas IVA Kurikulum 2013 Dengan Kemampuan Pemahaman Matematis - Annisa Nurhidayah; Anas Salahudin (Al-Aulad: Journal of Islamic Primary Education, 2022)
This study aims to determine the suitability of teaching materials in the textbook Senang Belajar Matematika 4 with the ability of students' mathematical understanding which is the reference in this analysis is an indicator of mathematical understanding ability. This research is a descriptive analysis type of research by taking the object of textbook Senang Belajar Matematika 4 as the data source. The data collection technique uses observation by filling out the observation sheet. Data analysis using content analysis and documentation analysis. Based on the results of this study, it shows that the teaching materials contained in the textbook Senang Belajar Matematika 4 are compatible with indicators of mathematical understanding, namely: 1) re-conveying the concepts that have been learned, 2) classifying objects based on the requirements that must be met to form a concept, 3) applying the concept in a systematic form, 4) presenting the concept in mathematical form, and 5) connecting a concept with other concepts. The textbook Senang Belajar Matematika 4 also refers to the 5M in the 2013 curriculum scientific approach.